Вы находитесь на странице: 1из 13

The Linear Equations of Higher Order

The linear differential equation of higher order n is an equation that can be written

is said to be homogeneous, whereas an equation

with g(x) not identically zero, is said to be nonhomogeneous.

DIFFERENTIAL OPERATORS

In calculus differentiation is often denoted bythe capital letter D—that is, dy/dx = Dy. The symbol D is
called a differential operator because it transforms a differentiable function into another function.

Higher-orderderivatives can be expressed in terms of D in a natural manner:

In general, we define an nth-order differential operatoror polynomial operator to be

SUPERPOSITION PRINCIPLE

1
EXAMPLE

LINEAR DEPENDENCE AND LINEAR INDEPENDENCE

WRONSKIAN

2
EXAMPLE
Find the Wronskian of {sin 2x, cos 2x}.
Solution:
sin 2𝑥 cos 2𝑥
sin 2𝑥 cos 2𝑥
𝑊 (sin 2𝑥 , cos 2𝑥) = [𝑑(sin 2𝑥) 𝑑(cos 2𝑥)] = [ ] = −2
2 cos 2𝑥 − 2 sin 2𝑥
𝑑𝑥 𝑑𝑥

EXAMPLE

3
HOMOGENEOUS LINEAR EQUATIONSWITH CONSTANT COEFFICIENTS

For the complementary function yc which is the solution to the homogeneous linear equation,

𝜑(𝐷)𝑦 = (𝑎0 𝐷 𝑛 + 𝑎1 𝐷 𝑛−1 + ⋯ + 𝑎𝑛−1 𝐷 + 𝑎𝑛 )𝑦 = 0


Is dependent on the nature of the roots of the auxiliary equation
𝑎0 𝑚𝑛 + 𝑎1 𝑚𝑛−1 + ⋯ + 𝑎𝑛−1 𝑚 + 𝑎𝑛 = 0.

CASE 1: When the n roots r1, r2, … ,rn of the auxiliary equation are real and distinct.
𝑦 = 𝐶1 𝑒 𝑟1 𝑥 + 𝐶2 𝑒 𝑟2 𝑥 + ⋯ + 𝐶𝑛 𝑒 𝑟𝑛 𝑥

CASE 2: When there are p(p≤n)equaland real roots r1 = r2 = … = rp of the auxiliary equation and the rest
are real and distinct.

𝑦 = 𝑒 𝑟𝑥 (𝐶1 + 𝐶2 𝑥 + ⋯ + 𝐶𝑝−1 𝑥 𝑝−2 + 𝐶𝑝 𝑥 𝑝−1 ) + 𝐶𝑝+1 𝑒 𝑟𝑝+1 𝑥 + ⋯ + 𝐶𝑛 𝑒 𝑟𝑛 𝑥

CASE 3: When the auxiliary equation has 2 conjugate complex roots 𝑟1 = 𝑎 + 𝑏𝑖 and 𝑟2 = 𝑎 − 𝑏𝑖, and
the rest are real and distinct.
𝑦 = 𝑒 𝑎𝑥 (𝐶1 cos 𝑏𝑥 + 𝐶2 sin 𝑏𝑥) + 𝐶3 𝑒 𝑟3 𝑥 + ⋯ + 𝐶𝑛 𝑒 𝑟𝑛 𝑥

CASE 4: When the conjugate complex roots 𝑎 ± 𝑏𝑖 occurs p times (p > 1) in the auxiliary equation and
the rest real and distinct.
𝑦 = 𝑒 𝑎𝑥 {(𝐶1 + 𝐶2 𝑥 + ⋯ + 𝐶𝑝−1 𝑥 𝑝−2 + 𝐶𝑝 𝑥 𝑝−1 ) cos 𝑏𝑥 + (𝑘1 + 𝑘2 𝑥 + ⋯ + 𝑘𝑝−1 𝑥 𝑝−2 + 𝑘𝑝 𝑥 𝑝−1 ) sin 𝑏𝑥}

Example:

Determine the solution of:

a. (𝐷3 − 4𝐷2 + 3𝐷)𝑦 = 0.

Solution:

The auxiliary equation of the given equation is

𝑚3 − 4𝑚2 + 3𝑚 = 0

4
𝑚 (𝑚 − 1)(𝑚 − 3) = 0

With roots 𝑟1 = 0; 𝑟2 = 1; 𝑎𝑛𝑑 𝑟3 = 3, which are all real and distinct (CASE 1!)

𝑦 = 𝐶1 𝑒 𝑟1 𝑥 + 𝐶2 𝑒 𝑟2 𝑥 + ⋯ + 𝐶𝑛 𝑒 𝑟𝑛 𝑥

𝑦 = 𝐶1 𝑒 (0)(𝑥) + 𝐶2 𝑒 (1)(𝑥) + 𝐶3 𝑒 (3)(𝑥)

𝑦 = 𝐶1 + 𝐶2 𝑒 𝑥 + 𝐶3 𝑒 3𝑥

b. 𝐷3 − 6𝐷 2 + 12𝐷 − 8 = 0

Solution:

The auxiliary equation of the given equation is

𝑚3 − 6𝑚2 + 12𝑚 − 8 = 0

(𝑚 − 2)(𝑚 − 2)(𝑚 − 2) = 0

With roots 𝑟1 = 𝑟2 = 𝑟3 = 2, which are all equal and repeated (CASE 2!)

𝑦 = 𝑒 𝑟𝑥 (𝐶1 + 𝐶2 𝑥 + ⋯ + 𝐶𝑝−1 𝑥 𝑝−2 + 𝐶𝑝 𝑥 𝑝−1 ) + 𝐶𝑝+1 𝑒 𝑟𝑝+1 𝑥 + ⋯ + 𝐶𝑛 𝑒 𝑟𝑛 𝑥

𝑦 = 𝑒 𝑟𝑥 (𝐶1 + 𝐶2 𝑥 + 𝐶3 𝑥 2 )

𝑦 = 𝑒 2𝑥 (𝐶1 + 𝐶2 𝑥 + 𝐶3 𝑥 2 )

c. (𝐷3 + 9𝐷)𝑦 = 0

Solution:

The auxiliary equation of the given equation is

𝑚3 + 9𝑚 = 0

𝑚(𝑚2 + 9) = 0

With roots 𝑟1 = 3𝑖 𝑎𝑛𝑑 𝑟2 = −3𝑖, 𝑤ℎ𝑒𝑟𝑒 𝑎 = 0 𝑎𝑛𝑑 𝑏 = 3; 𝑎𝑛𝑑 𝑟3 = 0, which are composed of 2 conjugate
complex roots 0 ± 3𝑖 and the rest is real and distinct (CASE 3!)

𝑦 = 𝑒 𝑎𝑥 (𝐶1 cos 𝑏𝑥 + 𝐶2 sin 𝑏𝑥) + 𝐶3 𝑒 𝑟3 𝑥 + ⋯ + 𝐶𝑛 𝑒 𝑟𝑛 𝑥

𝑦 = 𝑒 (0)(𝑥) (𝐶1 cos(3)(𝑥) + 𝐶2 sin(3)(𝑥)) + 𝐶3 𝑒 (0)(𝑥)

5
𝑦 = 1(𝐶1 cos 3𝑥 + 𝐶2 sin 3𝑥) + 𝐶3 (1)

𝑦 = 𝐶1 cos 3𝑥 + 𝐶2 sin 3𝑥 + 𝐶3

d. (𝐷4 + 18𝐷2 + 81)𝑦 = 0.

Solution:

The auxiliary equation of the given equation is

𝑚4 + 18𝑚2 + 81 = 0

(𝑚2 + 9)(𝑚2 + 9) = 0

With roots 𝑟1 = 𝑟2 = 3𝑖, 𝑎𝑛𝑑 𝑟3 = 𝑟4 = −3𝑖, 𝑤ℎ𝑒𝑟𝑒 𝑎 = 0 𝑎𝑛𝑑 𝑏 = 3; which are composed of conjugate
complex roots 0 ± 3𝑖 occurs p = 2 times (p > 1). (CASE 4!)

𝑦 = 𝑒 𝑎𝑥 {(𝐶1 + 𝐶2 𝑥 + ⋯ + 𝐶𝑝−1 𝑥 𝑝−2 + 𝐶𝑝 𝑥 𝑝−1 ) cos 𝑏𝑥 + (𝑘1 + 𝑘2 𝑥 + ⋯ + 𝑘𝑝−1 𝑥 𝑝−2 + 𝑘𝑝 𝑥 𝑝−1 ) sin 𝑏𝑥}

𝑦 = 𝑒 𝑎𝑥 {(𝐶1 + 𝐶2 𝑥) cos 𝑏𝑥 + (𝑘1 + 𝑘2 𝑥) sin 𝑏𝑥}

𝑦 = 𝑒 (0)(𝑥) {(𝐶1 + 𝐶2 𝑥) cos(3)(𝑥) + (𝑘1 + 𝑘2 𝑥) sin(3)(𝑥)}

𝑦 = (1){(𝐶1 + 𝐶2 𝑥) cos 3𝑥 + (𝑘1 + 𝑘2 𝑥) sin 3𝑥}

𝑦 = (𝐶1 + 𝐶2 𝑥) cos 3𝑥 + (𝑘1 + 𝑘2 𝑥) sin 3𝑥

𝑦 = (𝐶1 + 𝐶2 𝑥) cos 3𝑥 + (𝐶3 + 𝐶4 𝑥) sin 3𝑥

THE NON-HOMOGENEOUS LINEAR EQUATION WITH CONSTANT COEFFICIENTS

The differential equation

Has a solution of 𝑦 = 𝑦𝑐 + 𝑦𝑝 .

THE PARTICULAR INTEGRAL YP: THE PARTICULAR SOLUTION TO THE HOMOGENEOUS LINEAR
EQUATION

6
METHOD 1: UNDETERMINED COEFFICIENTS

This can only be applied to special types of right-hand function g(x), namely:

a. for 𝑔(𝑥) = 𝐾𝑥 𝑝 𝑒 𝑞𝑥 (𝑞 = 0 𝑎𝑛𝑑/𝑜𝑟 𝑞 ≠ 0); and

b. for 𝑔(𝑥) = 𝐾𝑥 𝑝 𝑒 𝑞𝑥 cos 𝑏𝑥 𝑜𝑟 𝑔(𝑥) = 𝐾𝑥 𝑝 𝑒 𝑞𝑥 sin 𝑏𝑥

where p is positive integer or zero; q and b are any real constants including zero; and K is any constant.

The point here is to find a particular solution, however the first thing to do is to find the complementary solution to
the differential equation. Recall that the complementary solution comes by treating the given DE as homogeneous,
g(x) = 0, then solving it.

For the particular solution, the method is quite simple. All that we need to do is look at g(x) and make a
guess as to the form of YP(t) leaving the coefficient(s) undetermined (and hence the name of the method).
Plug the guess into the differential equation and see if we can determine values of the coefficients. If we
can determine values for the coefficients then we guessed correctly, if we can’t find values for the
coefficients then we guessed incorrectly.

Rule 1: 𝒈(𝒙) = 𝑲𝒙𝒑 𝒆𝒒𝒙

a. For 𝑞 = 0 and 𝑎𝑛 ≠ 0 in 𝜑(𝐷)𝑦 = 𝑔(𝑥)

𝑦𝑝 = 𝐴𝑥 𝑝 + 𝐵𝑥 𝑝−1 + … + 𝐿𝑥 + 𝑀

b. For 𝑞 = 0 and 𝑎𝑛 = 0 in 𝜑(𝐷)𝑦 = 𝑔(𝑥)

𝑦𝑝 = (𝐴𝑥 𝑝 + 𝐵𝑥 𝑝−1 + … + 𝐿𝑥 + 𝑀)𝑥 𝑟

Where 𝑟 = 𝑛𝑢𝑚𝑏𝑒𝑟 𝑜𝑓 𝑡𝑖𝑚𝑒𝑠 0 𝑎𝑝𝑝𝑒𝑎𝑟𝑠 𝑎𝑠 𝑎 𝑟𝑜𝑜𝑡 𝑜𝑓 𝑡ℎ𝑒 𝑎𝑢𝑥𝑖𝑙𝑖𝑎𝑟𝑦 𝑒𝑞𝑢𝑎𝑡𝑖𝑜𝑛 𝜑(𝑚) = 0

c. For 𝑞 ≠ 0 and 𝑎𝑛 = 0 in 𝜑(𝐷)𝑦 = 𝑔(𝑥)

𝑦𝑝 = 𝑒 𝑞𝑥 (𝐴𝑥 𝑝 + 𝐵𝑥 𝑝−1 + … + 𝐿𝑥 + 𝑀)𝑥 𝑟

Where 𝑟 = 𝑛𝑢𝑚𝑏𝑒𝑟 𝑜𝑓 𝑡𝑖𝑚𝑒𝑠 𝑞 𝑎𝑝𝑝𝑒𝑎𝑟𝑠 𝑎𝑠 𝑎 𝑟𝑜𝑜𝑡 𝑜𝑓 𝑡ℎ𝑒 𝑎𝑢𝑥𝑖𝑙𝑖𝑎𝑟𝑦 𝑒𝑞𝑢𝑎𝑡𝑖𝑜𝑛 𝜑(𝑚) = 0

7
Rule 2: 𝑔(𝒙) = 𝑲𝒙𝒑 𝒆𝒒𝒙 𝐜𝐨𝐬 𝒃𝒙 𝒐𝒓 𝒈(𝒙) = 𝑲𝒙𝒑 𝒆𝒒𝒙 𝐬𝐢𝐧 𝒃𝒙

𝑦𝑝 = 𝑒 𝑞𝑥 (𝐴1 𝑥 𝑝 + 𝐵1 𝑥 𝑝−1 + … + 𝐿1 𝑥 + 𝑀1 )𝑥 𝑟 cos 𝑏𝑥 + 𝑒 𝑞𝑥 (𝐴2 𝑥 𝑝 + 𝐵2 𝑥 𝑝−1 + … + 𝐿2 𝑥 + 𝑀2 )𝑥 𝑟 sin 𝑏𝑥

Where 𝑟 = 𝑛𝑢𝑚𝑏𝑒𝑟 𝑜𝑓 𝑡𝑖𝑚𝑒𝑠 𝑞 + 𝑏𝑖 𝑎𝑝𝑝𝑒𝑎𝑟𝑠 𝑎𝑠 𝑎 𝑟𝑜𝑜𝑡 𝑜𝑓 𝑡ℎ𝑒 𝑎𝑢𝑥𝑖𝑙𝑖𝑎𝑟𝑦 𝑒𝑞𝑢𝑎𝑡𝑖𝑜𝑛 𝜑(𝑚) = 0

Example:

Determine a particular solution to


𝑦" − 4𝑦′ − 12𝑦 = 3𝒆5𝑥 .

Solution:

Recall that the complementary solution comes from solving,


𝑦" − 4𝑦′ − 12𝑦 = 0

The auxiliary equation will become


𝑚2 − 4𝑚 − 12 = 0
(𝑚 − 6)(𝑚 + 2) = 0
𝑚1 = −2; 𝑚2 = 6

Thus, the complementary solution is


𝑦𝑐 = 𝐶1 𝑒−2𝑥 + 𝐶2 𝑒6𝑥

For the particular solution, use Rule 1c

For (𝑥) = 3𝑒 5𝑥 : 𝑞 = 5, 𝑝 = 0; r = 0

𝑦𝑝 = 𝑒 𝑞𝑥 (𝐴𝑥 𝑝 + 𝐵𝑥 𝑝−1 + … + 𝐿𝑥 + 𝑀)𝑥 𝑟

𝑦𝑝 = 𝑒 5𝑥 (𝐴𝑥 0 )𝑥 0

8
𝑦𝑝 = 𝐴𝑒 5𝑥

Hence,

𝑦𝑝′ = 5𝐴𝑒 5𝑥

𝑦𝑝′′ = 25𝐴𝑒 5𝑥

Plugging into the differential equation gives

𝑦" − 4𝑦′ − 12𝑦 = 3𝒆5𝑥


(25𝐴𝑒5𝑥 ) – 4(5𝐴𝑒5𝑥 ) − 12(𝐴𝑒5𝑥 ) = 3𝒆5𝑥
−7(𝐴𝑒5𝑥 ) = 3𝒆5𝑥

3
For the coefficient of 𝑒 5𝑥 : −7𝐴 = 3 𝑜𝑟 𝐴 = −
7

𝑦𝑝 = 𝐴𝑒 5𝑥

3
𝑦𝑝 = − 𝑒 5𝑥
7
And

𝑦 = 𝑦𝑐 + 𝑦𝑝

3
𝑦 = 𝐶1 𝑒 −2𝑥 + 𝐶2 𝑒 6𝑥 − 𝑒 5𝑥
7

Example:

Determine a particular solution to


(𝐷2 + 2𝐷 + 5)𝑦 = 3𝑒 −𝑥 𝑠𝑖𝑛 𝑥 − 10.

Solution:

Recall that the complementary solution comes from solving,


(𝐷2 + 2𝐷 + 5)𝑦 = 0
𝑦" + 2𝑦′ + 5𝑦 = 0

The auxiliary equation will become


𝑚2 + 2𝑚 + 5 = 0

9
𝑚1 = −1 + 2𝑖; 𝑚2 = −1 − 2𝑖

Thus, the complementary solution is


𝑦𝑐 = 𝑒 𝑎𝑥 (𝐶1 cos 𝑏𝑥 + 𝐶2 sin 𝑏𝑥)

𝑦𝑐 = 𝑒 (−1)(𝑥) (𝐶1 cos 2𝑥 + 𝐶2 sin 2𝑥)


𝑦𝑐 = 𝑒 −𝑥 (𝐶1 cos 2𝑥 + 𝐶2 sin 2𝑥)

For the particular solution,

For (𝑥) = 3𝑒−𝑥𝑠𝑖𝑛 𝑥 : 𝑞 = −1, 𝑝 = 0, 𝑏 = 1, 𝑟 = 0 (𝑞 + 𝑏𝑖 = −1 + 𝑖 𝑑𝑜𝑒𝑠 𝑛𝑜𝑡 𝑎𝑝𝑝𝑒𝑎𝑟𝑎𝑠 𝑟𝑜𝑜𝑡)

Use Rule 2

𝑦𝑝 = 𝑒 𝑞𝑥 (𝐴1 𝑥 𝑝 + 𝐵1 𝑥 𝑝−1 + … + 𝐿1 𝑥 + 𝑀1 )𝑥 𝑟 cos 𝑏𝑥 + 𝑒 𝑞𝑥 (𝐴2 𝑥 𝑝 + 𝐵2 𝑥 𝑝−1 + … + 𝐿2 𝑥 + 𝑀2 )𝑥 𝑟 sin 𝑏𝑥

𝑦𝑝1 = 𝑒 (−1)𝑥 (𝐴1 𝑥 0 )𝑥 0 cos(1)(𝑥) + 𝑒 (−1)(𝑥) (𝐴2 𝑥 0 )𝑥 0 sin(1)(𝑥)

𝑦𝑝1 = 𝑒 −𝑥 (𝐴1 (1))(1) cos 𝑥 + 𝑒 −𝑥 (𝐴2 (1))(1) sin 𝑥

𝑦𝑝1 = 𝐴1 𝑒 −𝑥 cos 𝑥 + 𝐴2 𝑒 −𝑥 sin 𝑥

For (𝑥) = −10 : 𝑞 = 0, 𝑝 = 0, 𝑎𝑛𝑑 𝑎𝑛 = 10 ≠ 0


Use Rule 1a

𝑦𝑝2 = 𝐴𝑥 𝑝 + 𝐵𝑥 𝑝−1 + … + 𝐿𝑥 + 𝑀

𝑦𝑝 = 𝐴𝑥 0

𝑦𝑝 = 𝐴 = 𝐶

Therefore,

𝑦𝑝 = 𝑦𝑝1 + 𝑦𝑝2

𝑦𝑝 = 𝐴1 𝑒 −𝑥 cos 𝑥 + 𝐴2 𝑒 −𝑥 sin 𝑥 + 𝐶

𝑦𝑝 = 𝐴𝑒 −𝑥 cos 𝑥 + 𝐵𝑒 −𝑥 sin 𝑥 + 𝐶

𝑦𝑝 ′ = 𝐴[𝑒 −𝑥 (− sin 𝑥) + (−𝑒 −𝑥 )(cos 𝑥)] + 𝐵[𝑒 −𝑥 (cos 𝑥) + (−𝑒 −𝑥 )(𝑠𝑖𝑛𝑥)] + 0

10
𝑦𝑝′ = −𝐴𝑒 −𝑥 sin 𝑥 − 𝐴𝑒 −𝑥 cos 𝑥 + 𝐵𝑒 −𝑥 cos 𝑥 − 𝐵𝑒 −𝑥 sin 𝑥

𝑦𝑝′ = −𝐴𝑒 −𝑥 cos 𝑥 + 𝐵𝑒 −𝑥 cos 𝑥 − 𝐴𝑒 −𝑥 sin 𝑥 − 𝐵𝑒 −𝑥 sin 𝑥

𝑦𝑝′ = −(𝐴 − 𝐵)𝑒 −𝑥 cos 𝑥 − (𝐴 + 𝐵)𝑒 −𝑥 sin 𝑥

𝑦𝑝′ = −(𝐴 − 𝐵)𝑒 −𝑥 cos 𝑥 − (𝐴 + 𝐵)𝑒 −𝑥 sin 𝑥

𝑦𝑝′′ = −(𝐴 − 𝐵)[𝑒 −𝑥 (− sin 𝑥) + (−𝑒 −𝑥 )(cos 𝑥)] – (𝐴 + 𝐵)[𝑒 −𝑥 (cos 𝑥) + (−𝑒 −𝑥 )(𝑠𝑖𝑛𝑥)]

𝑦𝑝′′ = −(𝐴 − 𝐵)[−𝑒 −𝑥 sin 𝑥 − 𝑒 −𝑥 cos 𝑥] – (𝐴 + 𝐵)[𝑒 −𝑥 cos 𝑥 − 𝑒 −𝑥 sin 𝑥]

𝑦𝑝′′ = 𝐴𝑒 −𝑥 sin 𝑥 + 𝐴𝑒 −𝑥 cos 𝑥 − 𝐵𝑒 −𝑥 sin 𝑥 − 𝐵𝑒 −𝑥 cos 𝑥 − 𝐴𝑒 −𝑥 cos 𝑥 + 𝐴𝑒 −𝑥 sin 𝑥 − 𝐵𝑒 −𝑥 cos 𝑥 + 𝐵𝑒 −𝑥 sin 𝑥

𝑦𝑝′′ = 𝐴𝑒 −𝑥 sin 𝑥 − 𝐵𝑒 −𝑥 cos 𝑥 + 𝐴𝑒 −𝑥 sin 𝑥 − 𝐵𝑒 −𝑥 cos 𝑥

𝑦𝑝′′ = − 2𝐵𝑒 −𝑥 cos 𝑥 + 2𝐴𝑒 −𝑥 sin 𝑥

Plugging into the differential equation gives

𝑦" + 2𝑦′ + 5𝑦 = 3𝑒 −𝑥 𝑠𝑖𝑛 𝑥 − 10


[− 2𝐵𝑒−𝑥 cos 𝑥 + 2𝐴𝑒
−𝑥
sin 𝑥] + 2[−(𝐴 − 𝐵)𝑒−𝑥 cos 𝑥 − (𝐴 + 𝐵)𝑒−𝑥 sin 𝑥] + 5[𝐴𝑒−𝑥 cos 𝑥 + 𝐵𝑒−𝑥 sin 𝑥 + 𝐶] = 3𝑒 𝑠𝑖𝑛 𝑥 − 10 −𝑥

−𝑥
− 2𝐵𝑒 −𝑥 cos 𝑥 + 2𝐴𝑒 −𝑥 sin 𝑥 − 2𝐴𝑒−𝑥 cos 𝑥 + 2𝐵𝑒−𝑥 cos 𝑥 − 2𝐴𝑒−𝑥 sin 𝑥 − 2𝐵𝑒−𝑥 sin 𝑥 + 5𝐴𝑒−𝑥 cos 𝑥 + 5𝐵𝑒 sin 𝑥 + 5𝐶 = 3𝑒 𝑠𝑖𝑛 𝑥 − 10
−𝑥

−2𝐴𝑒 −𝑥 cos 𝑥 − 2𝐵𝑒 −𝑥 sin 𝑥 + 5𝐴𝑒 −𝑥 cos 𝑥 + 5𝐵𝑒 −𝑥 sin 𝑥 + 5𝐶 = 3𝑒 𝑠𝑖𝑛 𝑥 − 10


−𝑥

3𝐴𝑒 −𝑥 cos 𝑥 + 3𝐵𝑒 −𝑥 sin 𝑥 + 5𝐶 = 3𝑒−𝑥𝑠𝑖𝑛 𝑥 − 10

For the coefficients of


𝑒 −𝑥 cos 𝑥: 3𝐴 = 0; 𝐴 = 0

𝑒 −𝑥 sin 𝑥: 3𝐵 = 3; 𝐵 = 1

Constant: 5𝐶 = −10; 𝐶 = −2

Thus,

𝑦 = 𝑦𝑐 + 𝑦𝑝

𝑦 = [𝑒−𝑥 (𝐶1 cos 2𝑥 + 𝐶2 sin 2𝑥)] + [𝐴𝑒 −𝑥 cos 𝑥 + 𝐵𝑒 −𝑥 sin 𝑥 + 𝐶]

𝑦 = [𝑒−𝑥 (𝐶1 cos 2𝑥 + 𝐶2 sin 2𝑥)] + [(0)𝑒 −𝑥 cos 𝑥 + (1)𝑒 −𝑥 sin 𝑥 + (−2)]

𝑦 = 𝑒−𝑥(𝐶1 cos 2𝑥 + 𝐶2 sin 2𝑥) + 𝑒 −𝑥 sin 𝑥 − 2

11
METHOD 2: VARIATION OF PARAMETERS

12
13